Fungal amylases applied to the sweet potato starch for bioethanol production (Research, Society and Development, 2022)
Bioethanol is a sustainable energy source to help reducing the emission of pollutants into the global environment. In order to cope with that, the ethanol production technologies and use of efficient and low-cost substrates are developed. The objective of this research was to evaluate fungal amylases in sweet potato starch for bioethanol production by Saccharomyces cerevisiae in the laboratory. Endomelanconiopsis endophytica (1.40 U/mL), Neopestalotiopsis cubana (1.67 U/mL) and Fusarium pseudocircinatum (1.11 U/mL) with high enzymatic activities were selected and their amylases were tested for activity on sweet potato starch for bioethanol production. Simultaneous saccharification and fermentation was performed at 30° C and pH = 5.0. 17.3 - 88.1 (%) of bioethanol that was produced and compared to the expected theoretical yield. Therefore, amylases from these fungi simultaneously inserted on sweet potato starch and S. cerevisiae are potentially useful for bioethanol production.